Assessing anthropogenic influence on fire history during the Holocene in the Iberian Peninsula. (1st July 2022) - Sweeney, Luke; Harrison, Sandy P.; Linden, Marc Vander
Abstract: The relative importance of climate change and human activities in influencing regional fire regimes during the Holocene is still a matter of debate. The introduction of agriculture during the Neolithic provides an opportunity to examine the impact of human activities on fire regimes. Here, we examine changes in fire regimes across Iberia between 10, 000 and 3500 cal. BP, reconstructed using sedimentary charcoal records. We compare the regional fire history with estimates of changes in population size, reconstructed based on summed probability distributions of radiocarbon dates on archaeological material. We also compare the fire records and population reconstructions with the timing of the onset of agriculture across the region as indicated by archaeological data. For Iberia as a whole, there are two intervals of rapid population increase centred on ca. 7400 and ca. 5400 cal. BP. Periods of rapid population growth, either for the region as a whole or more locally, do not closely align with changes in charcoal accumulation. Charcoal accumulation had already begun to increase ca. 400 years prior to the onset of the Neolithic and continued to increase for ca. 750 years afterwards, indicating that changes in fire are not directly associated with the introduction of agriculture. Similarly, there is no direct relationship between changes in charcoal accumulation and later intervals of rapid population growth. There is also no significant relationship between population size and charcoal accumulation across the period of analysis. Our analyses show that the introduction of agriculture and subsequent increases in population are not directly linked with changes in fire regimes in Iberia and support the idea that changes in fire are largely driven by other factors such as climate. Highlights: The regional fire history of Iberia is characterised by millennial-scale variability during the Holocene. Regional population growth is broadly exponential, with intervals of faster growth at ca. 7400 and ca. 5400 cal. BP. Rapid changes in population size do not coincide with changes in regional fire. There is no direct impact of the onset of agriculture on regional fire regimes. There is no correlation between changes in population size and regional fire.